Global Patterns in Cratonic Mid‐Lithospheric Discontinuities From Sp Receiver Functions - Hannah E. Krueger; Isabella Gama; Karen M. Fischer (Geochemistry, Geophysics, Geosystems, 2021)
Abstract The goal of this study is to constrain the origins of layering in the seismic velocity structure within the cratonic mantle lithosphere (i.e. mid‐lithospheric discontinuities [MLDs]). For long‐lived stations in cratons worldwide, we calculated S‐to‐P converted phase receiver function stacks using time domain deconvolution and a k‐means algorithm to select robust, consistent receiver functions. Negative MLDs appear in only 50% of the receiver function stacks, indicating that negative MLDs are common but intermittent. The negative MLDs correspond to shear velocity drops of 1%–4%, which could be caused by layers of minerals created by metasomatism, although vertical layering in seismic anisotropy cannot be ruled out. In craton interiors, negative MLDs have a lower amplitude (<3% velocity drops) and can be explained by metasomatism of the original Archean mantle. Negative MLD amplitudes increase with decreasing upper mantle shear velocity (toward the outer margins of the cratons), but do not depend on the age of the craton. Thus, negative MLD amplitudes are not dominated by age‐related variations in the cratonic mantle composition, and, instead, are more strongly correlated with proximity to tectonic and metasomatic activity that occurred long after craton formation. Negative MLDs are less numerous among stations that have Paleoproterozoic and Archean thermotectonic ages, consistent with the view that shallow release of slab‐derived fluids during early “warm” subduction was less favorable for negative MLD formation. We also observe velocity gradients below 150 km at stations in craton boundaries and interiors, indicating the presence of seismic velocity changes at the cratonic lithosphere‐asthenosphere boundary and/or Lehmann discontinuity.